Information needs of the Finnish and Japanese hikikomori: a comparative study - Haasio, Ari; Naka, Hajime (Qualitative and Quantitative Methods in Libraries, 2019)
The hikikomori phenomenon is typically Japanese and it’s origins are in Japan. In this aticle we compare the information needs of Finnish and Japanese hikikomoris. Material was collected from Hikimomero discussion board (Finland) and Hikkyin2ch (Japan). Main research questions were: 1)What kind of information needs do Finnish and Japanese hikikomori express in discussion forums intended for hikikomori and 2)How do the information needs of Finnish and Japanese hikikomori differ from each other? Where are the possible differences based on and which variables may explain those differences? Analysis was made by quantitative and qualitative content analysis. The theoretical background is based on Reijo Savolainen's theory of everyday life information seeking and Elfreda Chatman's theory of a small world. The results show that cultural background has a great influence for one's information behaviour even though the belong to same subculture.